2020
DOI: 10.1371/journal.ppat.1009131
|View full text |Cite
|
Sign up to set email alerts
|

Multiple blood feeding in mosquitoes shortens the Plasmodium falciparum incubation period and increases malaria transmission potential

Abstract: Many mosquito species, including the major malaria vector Anopheles gambiae, naturally undergo multiple reproductive cycles of blood feeding, egg development and egg laying in their lifespan. Such complex mosquito behavior is regularly overlooked when mosquitoes are experimentally infected with malaria parasites, limiting our ability to accurately describe potential effects on transmission. Here, we examine how Plasmodium falciparum development and transmission potential is impacted when infected mosquitoes fe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 54 publications
2
74
0
Order By: Relevance
“…In addition to the impacts on immune recognition of Plasmodium oocysts associated with an additional blood meal, several recent studies have demonstrated that an additional feeding can also influence parasite growth [ 26 , 32 , 33 ]. In mosquitoes receiving an additional blood meal, P .…”
Section: Malariamentioning
confidence: 99%
“…In addition to the impacts on immune recognition of Plasmodium oocysts associated with an additional blood meal, several recent studies have demonstrated that an additional feeding can also influence parasite growth [ 26 , 32 , 33 ]. In mosquitoes receiving an additional blood meal, P .…”
Section: Malariamentioning
confidence: 99%
“…Regardless of the inhibitory mechanism, these results demonstrate that P. falciparum can be targeted via LLINs, IRS or ATSB throughout their development in the mosquito. This considerably increases the effective window of opportunity for a mosquito-targeted antimalarial intervention, given that even relatively modest increases in oocyst development time can significantly reduce the probability of parasite transmission due to the short mosquito lifespan (25, 45). Furthermore, slowing or preventing oocyst development could interact synergistically with both the transmission blocking effect of pre-infection antimalarial exposure, and with the life-shortening effects of insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…Shaw et al (2020) proved that previously infected An. gambiae females, when provided a second uninfected blood meal, present an increase in oocyst growth rates and faster accumulation of sporozoites in the salivary glands, which can indeed amplify local malaria transmission potential (Shaw et al, 2020). Therefore, this previously overlooked multiple feeding behavior is a justifiable current trend of investigation in vector-borne pathogen transmission.…”
Section: Multiple Blood-feedingsmentioning
confidence: 96%
“…Recently, it was shown that transgenic An. gambiae mosquitoes with reduced reproductive capacity have a significantly higher malaria transmission potential, due to an increase in parasite growth rates (Shaw et al, 2020). Due to the direct implications in currently proposed control strategies (e.g., eggless mosquitoes for population suppression) and the vacancy of descriptions of resource reallocation mechanisms in other insect vector species, this subject deserves a greater deal of attention in the field.…”
Section: Reproductive Physiology and Hormonal Regulationmentioning
confidence: 99%
See 1 more Smart Citation